Atlas of clinical hematology - Löffler, Helmut; Rastetter, Johann; Haferlach, Torsten (Springer, 2005)
This 6th edition of the atlas has integrated the 2001 WHO classification and made use of figures and descriptions to document recently described types of leukemia and lymphoma. The latter include leukemias of dendritic cells, rare lymphomas and persistent polyclonal B lymphocytosis, which takes a special place in the classification. The volume covers all the microscopic methods in hematology that form the basis of diagnosis as well as the results of modern immunologic, cytogenetic and molecular-genetic investigation. Special emphasis is placed on the cytogenetic and molecular-genetic characterization of biological entities that might form the basis for innovative therapies. Normal results and pathological findings are compared, and the various findings made during therapy are depicted. All in all the Atlas of Clinical Hematology represents a complete and helpful reference work which should be present in every hematologic and oncologic department as well as in clinical laboratories for online diagnostics and scientific research.
Keywords: Neoplasms; nádory; Cell Biology; biologie buňky; hematologie a transfuzní lékařství; hematologie; patologie; Hematology